99mTc radioimmunoscintigraphy of colorectal cancer. - Granowska, M. (Nature Publishing Group, 1990)
The monoclonal antibody PR1A3 against a normal colonic columnar cell surface antigen has been labelled with 99mTc and used for imaging colorectal cancer. High uptake in undifferentiated cancer is seen. The tumour to mucosa ratio was up to 63:1 and the percentage of the injected activity in the tumour up to 1.7 X 10(-2%)g-1. As 99mTc is continuously available in a Nuclear Medicine Department, on receipt of a request the study may be completed within 24 h enabling radioimmunoscintigraphy to be used routinely in the management of patients with colorectal cancer.